Hidden knowledge networks: Influence of invisible colleges on scientific research - Cano, Carlos Alberto Gómez (AWARI, 2023)
This review article explores the concept of the invisible college and its fundamental role in the formation and evolution of scientific research. Through an exhaustive analysis of the most relevant literature identified, we examined how these informal networks of scientists and academics facilitate the exchange of information, knowledge, and resources and assess their significant influence on research trends and the dissemination of scientific knowledge. A study was conducted with a qualitative and critical approach, operationalized through a scoping review design. The mechanisms through which these networks foster interdisciplinary collaboration and promote innovations, the challenges and opportunities for scientific policy and research management were analyzed, and strategies were suggested to recognize and enhance their value in the global scientific ecosystem. Finally, future directions are proposed to investigate the impact of these hidden networks on science to improve the understanding of their role in advancing knowledge.